Surgical Treatment and Outcomes of Adjacent Segmental Disease by Additional Extension-fixation Decompression and Fusion without Removing Prior Fixation by Using Domino Connector - Pisuitthanakan, MD, Satapong; Tantrakansakun, MD, Chakkraphan; Tantammaroj, MD, Pradit; Warachit, MD, Pairoj (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: Adjacent segmental disease (ASDis) represents symptomatic adjacent segment degeneration causing pain or neurological deficit. Revision lumbar decompression and extended spinal fusion remain the surgical gold standard. The surgical technique removes all prior implants (pedicle screw and rods) and applies the new implant to previous surgical sites while extending fixation across adjacent segments with fusion; however, it leads to soft tissue trauma, massive blood loss, prolonged operative time, and an increased fixation cost. This study aimed to present the use of a domino connector for connecting the old rod and new rod for extension fixation without removing prior fixation as an alternative technique. Methods: This study retrospectively analyzed the data of 14 patients with ASDis who underwent revision surgery with the use of a domino connector for connecting the old rod and new rod for extension fixation without the removal of prior fixation. Results: All the patients were aged 59–85 years with a mean age of 67.2 years. The mean duration of ASDis was 4.38 years postoperatively. The patients were grouped according to the modified MacNab criteria as follows: no patient in the excellent group, 12 patients in the good group, and two patients in the fair group. Conclusions: This surgical technique for treating failed back surgery syndrome reduces the extent of the surgery by employing rod connectors without prior instrument revision. It can serve as an alternative for the operative technique for treating patients with ASDis.